2020
DOI: 10.1074/jbc.ra119.011556
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA pncRNA-D reduces cyclin D1 gene expression and arrests cell cycle through RNA m6A modification

Abstract: pncRNA-D is an irradiation-induced 602-nt long noncoding RNA transcribed from the promoter region of the cyclin D1 (CCND1) gene. CCND1 expression is predicted to be inhibited through an interplay between pncRNA-D and RNA-binding protein TLS/FUS. Because the pncRNA-D–TLS interaction is essential for pncRNA-D–stimulated CCND1 inhibition, here we studied the possible role of RNA modification in this interaction in HeLa cells. We found that osmotic stress induces pncRNA-D by recruiting RNA polymerase II to its pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 60 publications
(126 reference statements)
0
34
0
Order By: Relevance
“…Furthermore, pncRNA-D is susceptible to m6A methylation and its methylation was dramatically decreased after osmotic stress or irradiation in HeLa cells [24]. Notably, it has been reported that the inhibition of methylation enhances the stability of pncRNA-D, thus promoting its interaction with FUS/TLS [24]. Therefore, the methylation process seems to ensure the control of cyclin D1 levels through two alternative ways.…”
Section: Pancrnas Support Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, pncRNA-D is susceptible to m6A methylation and its methylation was dramatically decreased after osmotic stress or irradiation in HeLa cells [24]. Notably, it has been reported that the inhibition of methylation enhances the stability of pncRNA-D, thus promoting its interaction with FUS/TLS [24]. Therefore, the methylation process seems to ensure the control of cyclin D1 levels through two alternative ways.…”
Section: Pancrnas Support Cell Proliferationmentioning
confidence: 99%
“…Accordingly, the inhibition of pncRNA-D by siRNA strategy or RNAseT1 treatment impairs the binding of FUS/TLS to the CCND1 promoter, further supporting the dependence of FUS/TLS from this specific ncRNA in the regulation of CCND1. Intriguingly, the methylation status of FUS/TLS as well as of pncRNA-D can affect the functionality of this molecular mechanism [24]. FUS/TLS contains two glycine-arginine rich (RGG) domains in its C-terminal region, which are directly involved in the binding to pncRNA-D [25].…”
Section: Pancrnas Support Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now understood that the m 6 A modification is required for the DDR to UV damage, providing proof of principle that RNA modifications can function in the DDR. A role for m 6 A at DSB sites is yet to be established, although m 6 A levels have been found to be altered in response to DSBs [ 127 , 135 ]. m 6 A and METTL3 were found to be elevated in glioma stem-like cells in response to IR, and silencing of METTL3 reduced DSB repair and enhanced the sensitivity to IR in these cells [ 135 ].…”
Section: Looking Ahead: Rna Modifications and The Ddr A Role For Rnamentioning
confidence: 99%
“…m 6 A and METTL3 were found to be elevated in glioma stem-like cells in response to IR, and silencing of METTL3 reduced DSB repair and enhanced the sensitivity to IR in these cells [ 135 ]. Moreover, the lncRNA pncRNA-D m 6 A modification levels were found to be reduced in response to IR or osmotic stress, which can induce DSBs, suggesting m 6 A can be modulated in response to DSBs [ 127 ].…”
Section: Looking Ahead: Rna Modifications and The Ddr A Role For Rnamentioning
confidence: 99%